(untitled) (Sociologisk Forskning, 2024)
The essay is a result of reading Erich Fromm’s book The Art of Loving, and its purpose is to explore the significance of trust in romantic relationships based on this book, focusing on the transition from falling in love to being in love. The transition from falling in love to being in love is the central theme, and it is in this process that trust is put to the test. According to Fromm, living in a lasting romantic relationship requires an art of loving. The essay argues that the art of loving has the potential to sustain trust, and it is trust that, in turn, safeguards love.